2021
DOI: 10.1111/1471-0528.16698
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth at different gestational periods and risk of impaired childhood growth, low childhood weight and obesity: a prospective birth cohort study

Abstract: Objective To examine the longitudinal associations of fetal growth with adverse child growth outcomes and to assess whether maternal metabolic factors modify the associations. Design Prospective cohort study. Setting Born in Guangzhou Cohort Study, China. Population A total of 4818 mother–child pairs. Methods Fetal growth was assessed according to estimated fetal weight (EFW) from 22 weeks of gestation until birth and the measurement of the birthweight. Fetal growth Z‐scores were computed from random effects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Well-trained and licensed ultrasonographers in GWCMC conducted these ultrasound measurements. As our previous study shows (15), the mean error of EFW estimation ([EFW − birth weight]/birth weight × 100%) is low (about 4%), and the correlation between two consecutive measurements of fetal biometric parameters performed within a week was high (r > 0.95). These results indicate good quality of the ultrasound data.…”
Section: Fetal Growth Assessmentmentioning
confidence: 71%
See 2 more Smart Citations
“…Well-trained and licensed ultrasonographers in GWCMC conducted these ultrasound measurements. As our previous study shows (15), the mean error of EFW estimation ([EFW − birth weight]/birth weight × 100%) is low (about 4%), and the correlation between two consecutive measurements of fetal biometric parameters performed within a week was high (r > 0.95). These results indicate good quality of the ultrasound data.…”
Section: Fetal Growth Assessmentmentioning
confidence: 71%
“…The resulting random effects from the models denote individual deviations from average size in early pregnancy (i.e., 22 weeks) and the average growth velocities in the three gestational intervals, which were converted into sex-specific z -scores before further analyses. More information on the modeling process can be found in our previous report ( 15 ). The same modeling approach was applied to generate AC and FL z -scores based on ultrasound measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the DOHaD theory, we speculated that fetal programming continued to play an important role in the growth patterns during the period of early childhood. Population-based cohort studies confirmed that fetal growth at different gestational periods was significantly associated with risks of impaired childhood growth, stunting, and obesity ( 26 , 27 ). Increased fetal growth at each period was negatively associated with stunting and underweight at the age of 3 years ( 26 ).…”
Section: Discussionmentioning
confidence: 91%
“…Population-based cohort studies confirmed that fetal growth at different gestational periods was significantly associated with risks of impaired childhood growth, stunting, and obesity ( 26 , 27 ). Increased fetal growth at each period was negatively associated with stunting and underweight at the age of 3 years ( 26 ). Conversely, intrauterine growth restriction infants were more prone to developing stunting when they were followed up to 18 months ( 27 ).…”
Section: Discussionmentioning
confidence: 91%